Determinants of mortgage lending: a time series analysis from South Africa - Davids, Megan (Graduate School of Business (GSB), 2023)
This study seeks to examine the influence of macroeconomic factors such as interest rates, inflation, GDP and house prices on mortgage lending in South Africa across different household income market segments (low, middle and high) as well as across different loan sizes (small, medium and large). Mortgage lending was further categorised by mortgage advances in rand value and volume and analysed using time series estimations techniques covering the period from Q4 2007 to Q4 2020. The study found a positive and significant long-term relationship between GDP on the proportion of mortgages advanced to low- and middle-income households in rand value and volume. This relationship held true on the proportion of small and medium-size mortgages advanced in rand value as well as medium-size mortgages in volume. Furthermore, house prices and interest rates also had a positive long-term relationship with mortgages advanced to the low- and middle-income market as well as inflation on the volume of loans advanced to the low-income market segment. GDP, house prices and interest rates had a negative long-term relationship with the proportion of mortgages advanced to high-income households in rand value and volume. The majority of loans are advanced to this market segment; thus results were found to be more in line with market theory and expectations. The impact of inflation was found to be mostly insignificant on the proportion of mortgages advanced to low-, middle- and high-income households in rand value but was found to be significant and negative for the proportion of mortgages advanced to middle- income households in volume. Inflation, interest rates and house prices had a highly significant and negative impact on the proportion of the volume of small mortgages advanced, which was expected as the lower end is much more sensitive to changes in interest rates and inflation. The findings highlight that market forces influences market segments differently and housing policy interventions should be aligned with macro-economic policy and consider changing market conditions and its influence on different market segments in order to be effective in assisting with the goal of economic redistribution through home ownership.